An Examination Of Risk Allocation Preferences In Public-Private Partnerships In Nigeria - Tolani, Olufemi Vincent (Journal of Sustainable Development Law and Policy, 2025)
Risk allocation preferences are important elements of Public-Private Partnerships (PPP), as the fundamental tension in many negotiations between the public and private sector in PPPs usually comes down to the question: who is responsible for managing a particular risk? Yet research literature suggests that risk allocation preferences phenomena have not been adequately studied; hence they remain poorly understood. This paper provides an empirical analysis and study of risk allocation preferences in PPPs in Nigeria. Research participants (spanning banking, construction, and public sector groups who were selected through a convenience sampling method) completed an online survey with Likert-type items within six months (i.e. between June and November 2011) to gauge probabilities of occurrence, risk impact and risk significance of 46 risk factors pertaining to PPP projects. As data did not meet the assumptions for parametric statistics, Mann-Whitney U tests were performed to evaluate the ranked differences in the independent variables (46 risk factors) between private and public sector groups. This paper shows that 27 (59%) out of the 46 risk factors are preferred to be allocated to the private sector, while 8 (17%) risk factors are to be allocated to the public sector and 11 (24%) of the risk factors are to be equally shared between the private and public sectors.